2015
DOI: 10.1007/s13369-015-1733-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of CuO Nanoparticles Suspension Induced by Laser Ablation in Liquid

Abstract: In the present study, copper oxide (CuO) colloidal nanoparticles (NPs) were synthesized using laser ablation of copper pellet immersed in deionized water. Pulsed Nd: YAG laser was used to irradiate the targets at different laser energies and various ablation times. NP suspensions were characterized by UV-Vis spectroscopy, XRD, and TEM. The absorption spectrum exhibited a peak at ∼275 nm and another peak with low intensity at ∼645 nm. The XRD pattern of the NPs proved the presence of (-111) and (112) planes ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(79 citation statements)
references
References 21 publications
12
64
1
2
Order By: Relevance
“…This is due to the fact that Cu NPs fabricated by LASiS method are in pure and colloidal form and the particle size is smaller as compared to nanoparticles produced by chemical reduction method. Khashan et al [31] measured the zone of inhibition of CuO with amoxicillin for E. coli ((26.0 ± 1.00) mm) with concentration of 1000 lg/ml. Ramyadevi et al [32] calculated zone of inhibition of S. aureus (21 mm) and E. coli (26 mm).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the fact that Cu NPs fabricated by LASiS method are in pure and colloidal form and the particle size is smaller as compared to nanoparticles produced by chemical reduction method. Khashan et al [31] measured the zone of inhibition of CuO with amoxicillin for E. coli ((26.0 ± 1.00) mm) with concentration of 1000 lg/ml. Ramyadevi et al [32] calculated zone of inhibition of S. aureus (21 mm) and E. coli (26 mm).…”
Section: Resultsmentioning
confidence: 99%
“…Results of this study demonstrated that E. coli was more sensitive than other bacteria species at a highest concentration of CuO NPs (1000 μg mL) with a inhibition zone of 26.0 ± 1.00 mm. 62 Sonia and coworkers (2016) investigated the antibacterial activity of CuO NPs in three different concentrations (12.5 μg/ml, 25 μg/ml and 50 μg/ml) by agar diffusion method against four pathogenic bacteria species: Serratia marcescens, Streptococcus pneumonia, Staphylococcus aureus, and Salmonella typhimurium. 61 The minimum inhibitory concentration (MIC) for all nanostructures was in the range of 12.5 μg/ml to 50 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of pH: Green synthesis of copper oxide nanoparticles using aqueous extract of Cordia myxa L. leaves was examined over a broad pH range (3)(4)(5)(6)(7)(8)(9)(10)(11). Variations in pH were highly affected the SPR of CuONPs.…”
Section: Different Parameters Were Optimized For the Biosynthesis Of mentioning
confidence: 99%
“…Their characters depended on certain trait such as size particle, distribution, morphology [4] and high surface/volume ratio [5]. Metal oxide nanoparticles obtained great attention for their potential applications in optoelectronics, nanodevices, nanoelectronics, nanosensors, information storage and catalysis [6,7].…”
Section: Introductionmentioning
confidence: 99%